Estetika dan Religi Penggunaan Rerajahan pada Masyarakat Bali - I Made Gami Sandi Untara; I Wayan Titra Gunawijaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Rerajahan is Balinese Hindu culture as a local product of the genus of Balinese Hindus. Hindus in Bali firmly believe that this rerajahan contains magic. The magical powers that can be generated by the rerajahan are used for sacred purposes, namely for things related to Hinduism which are called